Review guide and workbook for use with macroeconomics: analysis and policy - Reynolds, Lloyd G.; Porter, Richard C.; McCormick, Kenneth J. (Illinois Richard D. irwin Inc., 1985)
This review guide and workbook is designed to accompany the fifth edition of Lloyd G. Reynolds' textbook Macroeconomics: analysis and policy. Its purpose is to aid the student in learning the concepts, principles and analytical techniques presented in the textbook
osc 08/04/2019
Loans
Keywords: Macroeconomic policy